2023
DOI: 10.32471/exp-oncology.2312-8852.vol-42-no-4.15401
|View full text |Cite
|
Sign up to set email alerts
|

Modern views on the role of main components of stroma and tumor microinvironment in invasion, migration and metastasis

Abstract: Summary. The review presents modern ideas about tumor microenvironment, which most researchers recognize as the main “player” in tumor cell invasion, cell migration and metastasis. The current data on the main components of the stroma and the microenvironment, which play the role of the driving force in tumor progression, are analyzed. In particular, the review highlights the issues of origin, biological traits, phenotypic plasticity, functional heterogeneity of activated fibroblasts — myofibroblasts and tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Recent studies in human cancers have confirmed that the cellular and non-cellular composition of the tumour immune microenvironment (TME), particularly the activity of cytotoxic T cells, can be an essential factor that can predict clinical outcomes [ 36 , 52 ]. In the TME, the successive steps of initiation, growth and invasion at the primary tumour site, up to extravasation and colonisation of tumour cells at the metastasis site, are governed by a complex network of signalling pathways and intercellular interactions between tumour stroma components, immune cells and neoplastic cells [ 52 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in human cancers have confirmed that the cellular and non-cellular composition of the tumour immune microenvironment (TME), particularly the activity of cytotoxic T cells, can be an essential factor that can predict clinical outcomes [ 36 , 52 ]. In the TME, the successive steps of initiation, growth and invasion at the primary tumour site, up to extravasation and colonisation of tumour cells at the metastasis site, are governed by a complex network of signalling pathways and intercellular interactions between tumour stroma components, immune cells and neoplastic cells [ 52 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence indicates that the immunocompetent cells in the TME may contribute to tumour initiation and progression. Interactions between neoplastic cells and the innate immune cells may result in an environment and local niche that favours tumour spread and metastasis [ 39 , 52 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%